Morphological and Physiological Responses of Hybrid Aspen (Populus tremuloides Michx. × Populus tremula L.) Clones to Light In Vitro - Toms Kondratovičs; Mārtiņš Zeps; Diāna Rupeika; Pauls Zeltiņš; Arnis Gailis; Roberts Matisons (Plants, 2022)
Micropropagation of fast-growing tree genotypes such as the hybrid aspen (Populus tremuloides Michx. × Populus tremula L.) is increasing. The efficiency of micropropagation depends on the luminaires, hence luminescent electric diodes (LED), which emit light of a narrow spectrum, are gaining popularity. Mostly, different LEDs are combined to increase the photosynthetic efficiency. However, light also acts as an environmental signal, which triggers specific responses in plants, which are genotype specific, and regarding hybrid aspen, are likely affected by heterosis. In this study, morphological and physiological responses of clones of hybrid aspen with contrasting field performance to the spectral composition of illumination were studied in vitro. Among the 15 variables measured, area of leaves and concentration and ratio of chlorophyll a and b explained most of the variance (58.6%), thereby linking a specific combination of traits to productivity. These traits and their responses to light were affected by heterosis, as indicated by the clone-treatment interaction, particularly for the clone’s moderate productivity. The top-performing clones were little sensitive to illumination due to efficient photosystems. Nevertheless, illumination with wider spectral composition had generally positive effects on plantlet performance. Accordingly, clone-specific illumination protocols and luminaries capable of it are advantageous for the efficiency of micropropagation of hybrid aspen.